Characteristics and Geological Origin of Earthquakes and Tremor at Katla Volcano (S-Iceland) - Sgattoni, Giulia <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
Katla is a hazardous volcano in south Iceland, hosting a large caldera covered by the Mýrdalsjökull glacier. The last phreatomagmatic eruption occurred in 1918 and the present repose time is the longest known in history. The 2010 eruption of the neighbouring Eyjafjallajökull volcano prompted scientists’ concerns because the two volcanoes are tectonically connected. No visible eruption occurred, but in July 2011 a 23 hour tremor burst was associated with a glacial flood which caused damage to infrastructure. Deepening of the geothermally fed ice cauldrons, increased earthquake activity within the caldera and new seismicity on the south flank were also observed. Analysis of seismic data, including development of new location strategies, and a geological field study of the south flank were conducted to interpret the seismic sources. The tremor burst consisted of two volcano-related phases originated at the active cauldrons and a third phase generated by the flood. The increased seismicity inside the caldera and evidence of rapid ice melting may indicate that the volcano-related tremor was caused by a subglacial eruption. Alternatively, tremor may have been generated by hydrothermal boiling induced by the flood. The seismicity on the south flank consists of long-period repeating events occurring with regular time intervals, modulated by seasons (higher occurrence in summer). Because of the temporal evolution, hypocentre depth distribution and coincidence with the 2011 unrest, a volcano-related source is considered more likely than a glacial one. Hydrothermal processes may be easier to reconcile with the seasonal pattern than magmatic, although no direct indication of hydrothermal activity was found. A field survey revealed previously unknown flank eruption sites within the south flank. A magmatic source for the seismicity should therefore not be discarded. This observation is of major importance for hazard assessment of the south flank of Katla.